Preparation method of EPDM (Ethylene-Propylene-Diene Monomer) thermal insulation material with excellent mechanical and ablation isotropy

By using a combined process of insulating material preparation, the anisotropy problem of insulating material is solved, and the preparation of insulating material with excellent mechanical and ablation isotropy is achieved, which satisfactory thermal insulation material is satisfactory to meet the thermal insulation of solid rocket engines Material indicator requirements.

CN119505431APending Publication Date: 2025-02-25HUBEI SANJIANG AEROSPACE JIANGHE CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411771459.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-04
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the mixing, flaking and vulcanization of traditional thermal insulation materials, anisotropy problems caused by fiber orientation lead to influence the mechanical properties, ablation properties and dimensional shrinkage, and it is difficult to reduce the fiber orientation distribution while maintaining good mechanical properties.

Method used

The mixed machine is used to premix the vulcanization-related auxiliary materials, and then mix and extrude twice in the twin screw extruder. By adjusting the temperature and screw speed, the dispersion of the fiber filler in the rubber matrix is ​​significantly improved and the fiber orientation is reduced. distributed.

Benefits of technology

The advantages of thermal insulation material in the parallel and vertical outflow directions are achieved, and the gap is extremely small, ensuring the performance reliability of thermal insulation material in different directions and not affecting the material density and interface bonding performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505431A_ABST
    Figure CN119505431A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of thermal insulation materials, and particularly discloses a preparation method of an ethylene-propylene-diene monomer thermal insulation material with excellent mechanical and ablation isotropy, which comprises the following steps: S1, adding ethylene-propylene-diene monomer rubber and vulcanization-removing related auxiliary materials into an internal mixer for pre-mixing to obtain a rubber auxiliary bag; s2, crushing the rubber additive bag, and putting the crushed rubber additive bag into a first double-screw extruder for mixing; s3, extruding and pelletizing the rubber material obtained in S2, and then putting into a second double-screw extruder for secondary mixing; and S4, putting the material obtained in the step S3 into an internal mixer, adding vulcanization-related auxiliary materials for mixing, discharging sheets on an open mill after mixing is completed, and finally performing vulcanization molding. The double screws are used for mixing the thermal insulation material, the fiber orientation distribution trend is reduced, the thermal insulation material can still keep good mechanical and ablation resistance isotropy under the condition of more fiber filling, and other properties of the thermal insulation material are not affected.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of thermal insulation and ablation-resistant materials for solid rocket engines, and in particular to a method for preparing an EPDM thermal insulation material with excellent mechanical and ablation isotropy. Background Art

[0002] EPDM insulation material is widely used as the base rubber of the insulation layer in solid rocket engines due to its low density and excellent ablation resistance. In order to improve the ablation resistance of the insulation layer in solid rocket engines, some fillers such as chopped fibers and powders are often added to its formula. Due to the orientation of fibers, during the mixing, sheeting and vulcanization process of the insulation material, strong mechanical forces such as rolling or extrusion of the open mill roller cause the fibers to be oriented and distributed along the rolling direction, resulting in the insulation material showing anisotropic performance. This anisotropy affects the mechanical properties, ablation properties and dimensional shrinkage of the insulation material. The elongation at break of the insulation layer parallel to the sheeting direction is low. The anisotropy of the shrinkage rate can easily make the stress concentration problem of the insulation layer / steel interface more serious, which may cause the interface bonding failure; in addition, the patch direction needs to be strictly controlled during manual patching, and the dimensional control of vulcanized products such as insulation sleeves and prefabricated parts also needs to consider the direction, otherwise it is very easy to exceed the tolerance. Traditionally, the insulation layer is mixed and produced by using an internal mixer or an open mixer, and then thin sheets are produced by the open mixer. For fiber fillers with a relatively large aspect ratio, orientation is very likely to occur, resulting in anisotropy of the insulation material.

[0003] At present, the anisotropy of materials is mainly reduced by selecting fibers with small particle size and shape close to sphere or adding tackifier filling in the formulation system. CN 112225998 A discloses a thermal insulation material with excellent mechanical properties and a preparation method for high-energy propellants. From the perspective of formulation design, the problem of excessive difference in mechanical properties in different directions is reduced by introducing a variety of fibers and tackifier systems. However, the addition of a variety of fibers and tackifiers will inevitably affect the density of the thermal insulation material, as well as the bonding properties with the lining and steel interface, and is not suitable for a single fiber-filled thermal insulation layer formulation, which has certain limitations on the formulation design of the thermal insulation material. There is no public literature report on the method of solving the anisotropy of thermal insulation materials through mixing processes. Summary of the invention

[0004] The present invention provides a method for preparing an EPDM thermal insulation material with excellent mechanical and ablation isotropy. The prepared thermal insulation material has excellent mechanical and ablation properties in parallel and perpendicular directions of sheet output with a very small difference, does not affect the material density and interface bonding properties, and meets the index requirements of solid rocket engines for internal thermal insulation materials.

[0005] The technical solution of the present invention is to provide a method for preparing an EPDM thermal insulation material having excellent mechanical and ablation isotropy, characterized in that the method comprises the following steps: S1, adding EPDM rubber and auxiliary materials related to desulfurization into an internal mixer for pre-mixing to obtain a rubber additive package; S2, crushing the rubber additive package and putting it into the first twin-screw extruder for mixing, controlling the twin-screw barrel temperature to 80-120°C in zone 1-2, 160-240°C in zone 3-5, 160-240°C in zone 6-8, 160-250°C in zone 9-10, and 150-220°C in die zone; The rubber materials obtained in S3 and S2 are extruded and pelletized, and then put into the second twin-screw extruder for secondary mixing, and the twin-screw barrel temperature is controlled to be 1~2 zone: 70~120℃, 3~5 zone: 150~230℃, 6~8 zone: 150~230℃, 9~10 zone: 150~240℃, and die zone: 140~210℃; The materials obtained in S4 and S3 are put into an internal mixer, and the auxiliary materials related to vulcanization are added for mixing. After mixing, the sheets are produced on an open mixer, and finally vulcanization molding is carried out.

[0006] Optionally, the auxiliary material added in S1 includes organic fibers, which are short-cut or pulp-like fibers with a length of 1.0 to 6.0 mm.

[0007] Optionally, the organic fiber is one of aramid fiber (AF), polyimide fiber (PI), phenolic fiber (PF), poly(p-phenylene terephthalamide) fiber (PA), and polysulfone fiber (PSA).

[0008] Optionally, the pre-mixing temperature in S1 is 40-100° C., and the mixing time is 400-720 s.

[0009] Optionally, the rubber additive package in S2 is crushed, pelletized and sieved, and the sieve mesh size is 6-8 mm.

[0010] Optionally, the aspect ratio of the twin-screw extruder in S2 is (40-56):1; the screw speed is 50-120 rpm.

[0011] Optionally, the aspect ratio of the twin-screw extruder in S3 is (40-56):1; the screw speed is 60-140 rpm.

[0012] Optionally, in S4, the mixing temperature is 35-70° C., and the mixing time is 300-550 s.

[0013] Optionally, the internal mixer is a meshing type internal mixer, the rotor speed of the internal mixer is 28-51 rpm, and the upper push bolt pressure is 3-7 kg / cm 2 , the filling factor is 0.5~0.75.

[0014] Optionally, during the vulcanization in S3, the vulcanization temperature is 130-160° C. and the vulcanization time is 60-180 min.

[0015] The present invention has the following beneficial effects: The preparation method of the thermal insulation material of the present invention adopts an internal mixer to premix the auxiliary materials related to the desulfurization, thereby solving the problem that the pulp-like fiber has a long size and the powder mass is easily scattered, which is not conducive to direct processing. The rubber additive package is prepared to facilitate the subsequent screw extruder to feed and shear. The rubber material enters the first twin-screw extruder, and by adjusting the temperature of each section of the screw, the rubber molecular chain and the fiber filler are effectively broken under the strong shearing action of the screw, and the rubber material gradually changes from a solid state to a liquid state, and generates more free radicals that can react with fillers such as white carbon black, and the force between the fiber, white carbon black and the rubber matrix is ​​significantly enhanced. During the secondary mixing extrusion of the twin screw, by controlling the temperature and speed of the screw section, under the shearing action of the screw, the dispersion of fillers such as fibers in the rubber matrix is ​​significantly improved, the fiber orientation distribution trend is reduced, and the mechanical properties of the fiber-filled thermal insulation material are improved. Not only the mechanical strength, elongation at break and ablation performance in the vertical direction of the sheet are excellent, but also the various properties in the parallel direction of the sheet still meet the index requirements. The performance reliability of the thermal insulation material in different directions is guaranteed.

[0016] Compared with the mixing in traditional internal mixers and open mixers, the preparation method provided by the present invention adopts a twin-screw mixing method to reduce the fiber orientation and solve the anisotropy problem of the thermal insulation material. It can still maintain good mechanical properties when more organic fibers are filled, and does not affect other properties of the thermal insulation layer. The method has the advantages of more uniform dispersion, low equipment energy consumption, fast mixing rate, high efficiency, etc., and has high economic benefits. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 Schematic diagram of spline sampling during anisotropic mechanical property testing.

[0018] Figure 2 The present invention provides a process flow chart of the preparation method. DETAILED DESCRIPTION

[0019] The present invention is described in detail below in conjunction with specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and a specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0020] The experimental methods in the following examples are conventional methods unless otherwise specified. The raw materials, reagents, etc. used in the following examples are commercially available products unless otherwise specified.

[0021] Embodiment 1~5: The thermal insulation material formulas in Examples 1 to 5 are exactly the same, specifically 100 parts of EPDM rubber, 10 parts of aramid fiber AF, 15 parts of white carbon black SiO2, 6 parts of zinc oxide ZnO2, 12 parts of plasticizer dioctyl phthalate DOP, 8 parts of flame retardant ammonium polyphosphate APP, 2 parts of stearic acid YS, 1.5 parts of sulfur and 1.5 parts of accelerator DM. It should be noted that the formula is only for explaining the preparation method of the thermal insulation material, and thermal insulation materials of other formulas can also be prepared by the method provided by the present invention.

[0022] Examples 1 to 5 were prepared using the following steps: Figure 2 The difference lies in the twin-screw mixing process parameters, as shown in Table 1.

[0023] (1) Mixing: EPDM rubber, aramid fiber AF, white carbon black SiO2, zinc oxide ZnO2, plasticizer dioctyl phthalate DOP, flame retardant ammonium polyphosphate APP, and stearic acid YS were weighed in proportion and added into an internal mixer in sequence for premixing for 700 seconds. The mixing temperature was controlled at 40-60°C to obtain a rubber additive package.

[0024] The above additive package is poured into a small iron crusher for crushing, granulation and sieving, and the sieve mesh size is 8mm.

[0025] The sieved rubber material is fed into the first and second twin-screw extruders in sequence for two mixing and extrusion.

[0026] After extrusion, place the rubber material for a while. After the rubber material cools down, put it into an internal mixer, add sulfur and accelerator DM in proportion and mix until the mixture is uniform. The mixing temperature is 40~70℃.

[0027] The mixed rubber material is sheeted on the mixing mill and should be sealed and stored away from light before use.

[0028] The mixing process parameters of the two twin-screw extruders in Examples 1 to 5 are shown in Table 1.

[0029] Table 1. Twin-screw mixing parameters of Examples 1 to 5

[0030] (2) Sample preparation: Prepare 2.5 mm thick films along the parallel and perpendicular directions of the film output for testing mechanical, density, and interface bonding properties. Figure 1 shown.

[0031] Oxyacetylene ablation parts are prepared by parallel and vertical sample preparation processes. Parallel sample preparation process: 4 to 5 test pieces are stacked in the mold cavity and pressed by a flat vulcanizer. The orientation direction of the short fibers in the ablation sample is theoretically parallel to the upper and lower bottom surfaces of the sample. Vertical sample preparation process: The test piece is cut into rectangular strips along the vertical direction of the sheet, rolled into a cylinder and placed in the mold cavity, and prepared by a flat vulcanizer. Vulcanization conditions: 160℃×80min×3MPa.

[0032] (3) Performance test: The various properties of the insulation materials are tested in accordance with the relevant standards and specifications. The specific results are shown in Table 3.

[0033] The testing equipment and methods used for performance testing are: The mechanical properties were tested by Instron 5967 of Instron Company of the United States. The tensile strength and elongation at break were tested according to the standard "GB / T 528~2009 Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber", the test temperature was 23℃, and the tensile rate was 500mm / min. The density was tested according to the standard "QJ 917A~1997 Density determination method for composite solid propellants, linings and insulation materials", and the test temperature was 23℃. The oxygen-acetylene line ablation rate was determined according to the provisions of "GJB323B~2018 Ablation Test Method for Ablative Materials", and the test conditions were: nozzle diameter 2mm, ablation distance 10mm, oxygen pressure 0.4MPa, acetylene pressure 0.095MPa, oxygen flow rate 1512L / h, acetylene flow rate 1116L / h, oxygen-acetylene mixing ratio 1.35, and ablation time 20s. The interface bonding performance is tested according to the D-type specimen specified in "Q / QJB 349-2020 Test Method for Interface Bonding Strength of Solid Rocket Engine Combustion Chamber", with a test temperature of 23°C and a tensile rate of 50 mm / min.

[0034] Comparative Example 1: (1) Mixing: EPDM rubber, aramid fiber AF, white carbon black SiO2, zinc oxide ZnO2, plasticizer dioctyl phthalate DOP, flame retardant ammonium polyphosphate APP, stearic acid YS, sulfur S and accelerator DM were weighed according to the formula of Examples 1 to 5, and added into an internal mixer in sequence for mixing.

[0035] When preparing rubber, pay attention to controlling the mixing temperature at 50~100℃, avoid adding vulcanizers and accelerators when the temperature is too high, prevent the rubber from scorching, and affect the material performance and use. The correct mixing operation is to place the rubber for a period of time before adding the vulcanizer and accelerator, and then add them after the rubber cools down, and control the mixing temperature to 40~70℃. The mixed rubber should be sealed and stored away from light before use.

[0036] (2) Sheeting: Pass the mixed rubber material through an open mixing mill for 8 times and then sheet it for later use.

[0037] (3) Sample preparation and performance testing are the same as in the embodiment. The performance test results are shown in Table 3.

[0038] Comparative Examples 2 to 5: The preparation method and testing method of the insulation materials of Comparative Examples 2 to 5 are the same as those of the embodiment, except for the twin-screw mixing process parameters. The mixing process parameters of the two twin-screw extruders of Comparative Examples 2 to 5 are shown in Table 2.

[0039] Table 2. Twin screw mixing parameters for comparative examples 2 to 5

[0040] Table 3 shows the thermal insulation material performance data of the embodiments and comparative examples.

[0041] Table 3 Comparison of thermal insulation material properties of the embodiments and comparative examples

[0042] The index requirements of the EPDM insulation layer and the performance levels of the embodiments and comparative examples are shown in Table 4.

[0043] Table 4. EPDM insulation layer index requirements and performance levels of examples and comparative examples

[0044] It can be seen from the data in Table 3 and Table 4 that the density of the comparative EPDM insulation material in the vertical sheeting direction (i.e., direction A) is comparable to that of the embodiment, and the mechanical properties, oxyacetylene line ablation rate of vertical sample preparation and interface properties basically meet the index requirements, but although the tensile strength in the parallel sheeting direction (i.e., direction B) is high, the elongation at break is low, which can no longer meet the index requirements for mechanical properties under special conditions of the engine. At the same time, the oxyacetylene line ablation rate of the samples prepared in parallel and vertically is quite different, and the ablation resistance of the samples prepared in parallel is poor, which can no longer meet the higher requirements of the engine for ablation performance and anti-scouring performance. This is because under the vertical sample preparation process, the orientation direction of the fibers in the sample is parallel to the direction of the high-temperature and high-speed airflow of oxyacetylene. During the ablation process, the fibers inside the sample can play a certain riveting and consolidation role on the carbonized layer particles, effectively preventing the carbonized layer particles from falling off. At the same time, the large amount of gas generated after ablation can be quickly transmitted outward along the fiber direction, thereby reducing the temperature inside the sample and the expansion of the surface carbon layer, making the carbonized layer after ablation less likely to fall off, improving the anti-scouring performance of the carbonized layer, and the ablation rate of the sample is low. Under the parallel sample preparation process, the orientation direction of the fibers in the sample is perpendicular to the direction of the high-temperature and high-speed airflow of oxyacetylene. During the ablation process, the interaction force between the fibrous structure in the carbonized layer and the original rubber matrix is ​​weak, resulting in the inability of the short fibers to play a riveting and consolidation role on the carbonized layer particles, causing the carbon layer and the matrix rubber to be delaminated, causing part of the carbonized layer to fall off. At the same time, the gas generated during the ablation process cannot be smoothly conducted out of the surface of the ablated carbon layer, causing the carbon layer to expand, and then the heat continues to penetrate into the material, the material is further carbonized and ablated, and the ablation rate is relatively high.

[0045] The thermal insulation material prepared by the embodiment of mixing with a twin-screw extruder and an internal mixer not only has good mechanical properties in the direction perpendicular to the sheet-out direction, but also has excellent mechanical properties in the direction parallel to the sheet-out direction, which is basically equivalent to the elongation at break in the vertical direction, and can fully meet the engine's requirements for the mechanical properties of the thermal insulation layer; at the same time, the density is low, and the negative mass of the engine will not be significantly increased under the same thickness, and it has good adhesion to the shell interface; in addition, the samples prepared in parallel and vertical manners have better ablation resistance and erosion resistance, and the ablation rates of the two samples are at the same level, which meets the engine's requirements for the ablation resistance of the thermal insulation layer. This further illustrates that the use of a twin-screw extruder can mix the fiber filler evenly and shear the fiber to a smaller particle size, so that the anisotropy of the thermal insulation layer is almost non-existent.

[0046] The above embodiments describe the preferred implementation of the present invention, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing an EPDM thermal insulation material having excellent mechanical and ablation isotropy, characterized in that: The following steps are involved: S1, adding EPDM rubber and auxiliary materials related to desulfurization into an internal mixer for pre-mixing to obtain a rubber additive package; S2, crushing the rubber additive package and putting it into the first twin-screw extruder for mixing, controlling the twin-screw barrel temperature to 80-120°C in zone 1-2, 160-240°C in zone 3-5, 160-240°C in zone 6-8, 160-250°C in zone 9-10, and 150-220°C in die zone; The rubber materials obtained in S3 and S2 are extruded and pelletized, and then put into the second twin-screw extruder for secondary mixing, and the twin-screw barrel temperature is controlled to be 1~2 zone: 70~120℃, 3~5 zone: 150~230℃, 6~8 zone: 150~230℃, 9~10 zone: 150~240℃, and die zone: 140~210℃; The materials obtained in S4 and S3 are put into an internal mixer, and the auxiliary materials related to vulcanization are added for mixing. After mixing, the sheets are produced on an open mixer, and finally vulcanization molding is carried out.

2. The preparation method according to claim 1, characterized in that: The auxiliary materials added in S1 include organic fibers, which are short-cut or pulp-like fibers with a length of 1.0 to 6.0 mm.

3. The preparation method according to claim 2, characterized in that: The organic fiber is one of aramid fiber (AF), polyimide fiber (PI), phenolic fiber (PF), poly(p-phenylene terephthalamide) fiber (PA) or polysulfone fiber (PSA).

4. The preparation method according to claim 1, characterized in that: The pre-mixing temperature in S1 is 40-100°C, and the mixing time is 400-720s.

5. The preparation method according to claim 1, characterized in that: The rubber additive package in S2 is crushed, diced and sieved, and the sieve aperture is 6~8mm.

6. The preparation method according to claim 1, characterized in that: The length-to-diameter ratio of the twin-screw extruder in S2 is 40-56:1; the screw speed is 50-120 rpm.

7. The preparation method according to claim 1, characterized in that: The length-to-diameter ratio of the twin-screw extruder in S3 is 40-56:1; the screw speed is 60-140 rpm.

8. The preparation method according to claim 1, characterized in that: In S4, the mixing temperature is 35~70°C and the mixing time is 300~550s.

9. The preparation method according to any one of claims 1 to 8, characterized in that: The internal mixer is a meshing type internal mixer, the rotor speed of the internal mixer is 28-51 rpm, and the upper push bolt pressure is 3-7 kg / cm 2 , the filling factor is 0.5~0.

75.

10. The preparation method according to any one of claims 1 to 8, characterized in that: During vulcanization in S3, the vulcanization temperature is 130-160°C, and the vulcanization time is 60-180 minutes.